Utilization Edmodo Application in Study Bahasa Indonesia - Annisa Noor Ramadhani; Reni Nur Eriyani (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
This study is a type of qualitative research. This study aims to describe the use of the Edmodo platform in learning bahasa Indonesia. The data analysis method used in this research is content analysis. This analysis method is used to describe the object, namely what features can be used for learning bahasa Indonesia. The edmodo platform was developed in 2008 by Nic Borg dan Jeff O’hara. Based on the results of the analysis, there are eight features in edmodo that can be used for the learning process.